2020
DOI: 10.3389/fpls.2020.579120
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of an Antisense RNA of Maize Receptor-Like Kinase Gene ZmRLK7 Enlarges the Organ and Seed Size of Transgenic Arabidopsis Plants

Abstract: Leucine-rich repeat (LRR)-receptor-like protein kinases (LRR-RLKs) play vital roles in plant growth, development, and responses to environmental stresses. In this study, a new LRR-RLK gene, ZmRLK7 , was isolated from maize, and its function within plant development was investigated through ectopic expression in Arabidopsis . The spatial expression pattern analysis reveals that ZmRLK7 is highly expressed in embryos prior to programmed cell dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…ZmRLK7 encodes a putative LRR-RLK in maize, and overexpression of ZmRLK7 increased the organ size and seed weight. ZmRLK7 restricts both cell expansion and proliferation to play key roles in regulating the petal size in maize (He et al 2020). These results suggested that LRR-RLK kinases play important roles in regulating seed size/weight in plant species.…”
Section: Candidate Gene Prediction For 100-seed Weight In Soybeanmentioning
confidence: 85%
See 2 more Smart Citations
“…ZmRLK7 encodes a putative LRR-RLK in maize, and overexpression of ZmRLK7 increased the organ size and seed weight. ZmRLK7 restricts both cell expansion and proliferation to play key roles in regulating the petal size in maize (He et al 2020). These results suggested that LRR-RLK kinases play important roles in regulating seed size/weight in plant species.…”
Section: Candidate Gene Prediction For 100-seed Weight In Soybeanmentioning
confidence: 85%
“…It showed that Glyma.19G143300 shared more similarity with the LRR-RLK protein XIAO from rice (Fig. 5g), which has been shown to control seed size (He et al 2020). These results suggest that Glyma.19G143300 gene in soybean might also play an important role in controlling seed size/weight as the other known LRR-RLK genes.…”
Section: Sequence Variation Of the Candidate Genes For 100-seed Weightmentioning
confidence: 99%
See 1 more Smart Citation
“…On chromosome A09 and A11, Gh_A09G1499 , Gh_A09G1610 , Gh_A11G0179 , and Gh_A11G0252 belonged to the protein kinase superfamily which played fundamental roles in the modulation of plant growth and development, including seed development, dormancy and germination, seedling and root growth, flowering, fruit development, and ripening and leaf senescence ( Halford and Hey, 2009 ; Wang et al, 2020 ). Overexpression of the receptor protein kinase gene ZmRLK 7 in Arabidopsis reduced the plant height, organ size (e.g., petals, silique, and seeds) and seed weight ( He et al, 2020 ). The kinase-associated protein phosphatase (KAPP) in Arabidopsis was negatively involved in ABA-mediated seed germination and early seedling growth ( Lu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a natural antisense RNA was shown to be involved in the regulation of MADS AFFECTING FLOWERING4 (MAF4) in Arabidopsis (Zhao et al, 2018 ). The overexpression of an antisense RNA of the maize gene ZmRLK7 in Arabidopsis resulted in regulating plant architecture and organ size formation (He et al, 2020 ). An antisense RNA may regulate target gene expression using different mechanisms.…”
Section: Discussionmentioning
confidence: 99%